Frequency of Stone Free Rate Following Laser Lithotripsy for the Management of Ureteric Calculi in the Tertiary Care Centre of Lalitpur, Nepal - Alam, Mohammad Nasim; Shrestha, Binod; Batajoo, Rajesh; Kasaju, Atul (Nepal Medical College Journal, 2025)
Urolithiasis is one of the most common diseases of the urinary tract. The lifetime prevalence of urinary stones is around 1 to 15%, and the peak age of incidence is at 30 years. Ureteric stones account for 20% of the calculi in urolithiasis. Different modalities are being used for intracorporeal stone fragmentation such as pneumatic, electrohydraulic, ultrasonic, and laser lithotripsy. Ureteroscopy (URS) is the primary modality for management of ureteral stones. Laser lithotripsy is an established endourological modality. The aim of proposed synopsis is to determine the frequency of stone-free rate (SFR) following laser lithotripsy for the management of ureteric calculi. This was a hospital based descriptive cross-sectional study which conducted between 26th May 2022 and 27th November 2022, at Department of Urology, B & B Hospital. Of 71 patients, the mean age of the patients was 44.79±7.92 years. The frequency of successful stone clearance was observed in 62 (87.3%) patients. The mean size of ureteric calculi was 5.98 ±1.28 cm and the mean duration of ureteric stone disease was 4.14 ±0.91 months. Majority of the patients reported stone free rate following laser lithotripsy for the management of ureteric calculi.